Nucleolar PARP-1 Expression Is Decreased in Alzheimer’s Disease: Consequences for Epigenetic Regulation of rDNA and Cognition - Jianying Zeng; Jenny Libien; Fatima Shaik; Jason Wolk; A. Iván Hernández (Neural Plasticity)
Synaptic dysfunction is thought to play a major role in memory impairment in Alzheimer’s disease (AD). PARP-1 has been identified as an epigenetic regulator of plasticity and memory. Thus, we hypothesize that PARP-1 may be altered in postmortem hippocampus of individuals with AD compared to age-matched controls without neurologic disease. We found a reduced level of PARP-1 nucleolar immunohistochemical staining in hippocampal pyramidal cells in AD. Nucleolar PARP-1 staining ranged from dispersed and less intense to entirely absent in AD compared to the distinct nucleolar localization in hippocampal pyramidal neurons in controls. In cases of AD, the percentage of hippocampal pyramidal cells with nucleoli that were positive for both PARP-1 and the nucleolar marker fibrillarin was significantly lower than in controls. PARP-1 nucleolar expression emerges as a sensitive marker of functional changes in AD and suggests a novel role for PARP-1 dysregulation in AD pathology.